Kebijakan Hukum Pengaturan Penggunaan Kendaraan Listrik Dalam Penguatan Ketahanan Energi Nasional - I Nengah Nuarta; Mochamad Sukedi (Warmadewa Press, 2024)
A number of government policies to accelerate the use of electric vehicles are outlined in a number of statutory provisions. The legal umbrella for the use of electric vehicles was first outlined in Presidential Regulation Number 55 of 2019 concerning the Acceleration of the Battery-Based Electric Motorized Vehicle Program. Based on the background above, researchers are very interested in studying: 1) How are electric vehicles currently regulated in Indonesia? and 2) What is the ideal arrangement for electric vehicles to strengthen sustainable energy security in Indonesia? The type of research used in this research is normative legal research. The legal material analysis technique applied in this research involves describing what is the problem, explaining the problem (explanation), examining the problem (evaluation) and providing arguments from the results of the evaluation. The regulation of electric vehicles in Indonesia is currently regulated in Presidential Decree No. 55 of 2019, which is the initial regulation that became the legal umbrella for Indonesian electric vehicles, then derivatives such as PP No. 73 of 2019 which regulates the imposition of Sales Tax on Luxury Goods (PPnBM). Regulation of electric vehicles is ideal in strengthening sustainable energy security in Indonesia by advancing and regulating the biofuel industry, lithium battery industry and electric vehicles. In the future, the government can target public transportation vehicles to switch to using electric power with batteries.